Estrategia visual-gráfica para desarrollar la atención en los niños y niñas de preparatoria de la escuela “Vicente Bastidas Reinoso” de la ciudad de Loja, en el período 2019-2020. - Armijos Ruales, Diana Carolina (2021)
The research entitled VISUAL-GRAPHIC STRATEGY TO DEVELOP ATTENTION IN HIGH SCHOOL BOYS AND GIRLS OF THE “VICENTE BASTIDAS REINOSO” SCHOOL OF THE CITY OF LOJA, IN THE PERIOD 2019-2020; Its general objective was to determine the incidence of the visual-graphic strategy in the development of attention in high school boys and girls, in the research carried out it was experimental, specifically pre-experimental; quantitative approach; descriptive and correlational scope. The methods were used: scientific, analytical-synthetic, inductive-deductive and statisticaldescriptive. The investigated population was comprised of 44 children and 2 teachers from the Vicente Bastidas Reinoso school, with a non-probabilistic sample of 21 students and 1 teacher, due to the fact that this subgroup presented low levels of attention, characteristics that allowed the development of the research. The instrument used for the diagnosis was the Guide for the evaluation of attention adapted from the Guide for the detection and evaluation of difficulties in attention and memory of the Plurinational State of Bolivia, which served to evaluate the levels of attention in which children were . The results showed that in selective attention 57% at the regular level rose to 81% at the very good level, in focused attention 85% at the regular level rose to 81% at the very good level, in divided attention the 90% at the regular level rose to 76% at the very good level and finally, in sustained care, 71% at the regular level rose to 90% at the very good level; Obtaining a total average of 76% of the investigated population was at a regular level in selective, focused, sustained and divided attention, presenting difficulties when concentrating, executing and completing different proposed school activities. Regarding the proposal designed through playful activities based on images, they showed that 85% of the children were at the acquired level, 13% at the level in process and 2% at the beginning level. The final diagnosis showed a total mean of 82% in the very good level in the four types of care mentioned. Therefore, it is concluded that the alternative proposal based on the visual-graphic strategy had a remarkable effectiveness in the development of children's attention, specifically in selective, focused, divided and sustained attention as in their attention levels, whose results were corroborated with the data obtained from the application of the pre and post test, allowing raising the level of attention from regular to very good, in children from 5 to 6 years old.